2019
DOI: 10.3389/fped.2019.00038
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Overweight and Obesity Among Children and Adolescents With Autism Spectrum Disorder and Associated Risk Factors

Abstract: Introduction: Prevalence of obesity in Autism Spectrum Disorder (ASD) has been reported to be higher than in the general population. Determining prevalence may help increase awareness of obesity in ASD and potentially lead to initiatives to reduce obesity. In order to understand obesity in ASD children, common risk factors were assessed including physical activity, feeding problems and sleep disturbances. Methods: This is a cross-sectional study performed at the Child Develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
31
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 43 publications
(49 reference statements)
5
31
0
3
Order By: Relevance
“…It is likely that an abnormal amount of Firmicutes could lead to a surplus amount of carbohydrates in the bloodstream, causing neurological and behavioral problems associated with ASD. This also explains the high rate of obesity among teens with autism [ 38 ] as a higher Firmicutes/Bacteroidetes ratio has been linked to excess body fat in previous studies [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 94%
“…It is likely that an abnormal amount of Firmicutes could lead to a surplus amount of carbohydrates in the bloodstream, causing neurological and behavioral problems associated with ASD. This also explains the high rate of obesity among teens with autism [ 38 ] as a higher Firmicutes/Bacteroidetes ratio has been linked to excess body fat in previous studies [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 94%
“…From 12,100 articles retrieved, 110 (62 on ASD, 43 on ADHD and 5 on both) were eligible for inclusion (Tables S2 and S3). After excluding multiple articles on duplicate investigations 31–41 and studies that mixed obesity and overweight data, 42–45 54 studies on ASD 46–99 and 46 studies on ADHD 91–94,99–140 were separately included for quantitative analysis.…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that the majority of parents of children with ASD agreed that having a nutrition module would benefit them mainly in assisting in meal planning and food provision for their child. Several key factors need to be considered in developing nutrition modules such as a visually based, interactive format and the need to be culturally appropriate [68]. This is to ensure that effective communication can be delivered as a crucial first step in advancing one's understanding [69] towards nutritional knowledge.…”
Section: Theme 6: the Needs To Have A Nutrition Module Or Guidelines mentioning
confidence: 99%